Fatal Taxus baccata ingestion with perimortem serum taxine B quantification. (20th October 2016) - Arens, Ann M.; Anaebere, Tiffany C.; Horng, Howard; Olson, Kent
Abstract: Introduction: Common yew ( Taxus baccata ) is a common decorative evergreen shrub with potentially fatal toxicity hallmarked by seizure, arrhythmia and cardiovascular collapse if ingested. Taxine B has been identified as one of the most cardiotoxic taxine alkaloids in Taxus spp, and another alkaloid, 3, 5-dimethoxyphenol (3, 5-DMP), is used as a marker of ingestion. We present a fatal case of ingestion of yew with perimortem serum and gastric taxine B, and 3, 5-DMP concentrations. Case presentation: A 22-year-old woman was brought to the emergency department (ED) from a nearby botanical garden after she was found apneic and pulseless after a witnessed generalized tonic clonic seizure. The patient was found to have a wide complex rhythm with persistent cardiovascular collapse and expired despite maximal supportive care in the ED. A baggie of plant material was found on the patient, identified as Taxus baccata . Perimortem serum and gastric samples were analyzed to quantify serum and gastric taxine B and 3, 5-DMP concentrations. Results: Perimortem serum showed a 3, 5-DMP concentration of 86.9 ng/mL, and taxine B of 80.9 ug/mL. Conclusion: We report a perimortem serum and gastric taxine B and 3, 5-DMP concentrations in a fatal case of T. baccata toxicity.